COMPRESSIONAL CHARACTERISTICS OF Piper Guineense FRUIT - Bakre Lateef Gbenga; Ayodele Damilola (Indonesian Journal of Pharmacy, 2013)
The dried fruit of Piper guineense is widely used for its antibacterial and antifungal properties. The objective of this present study was to examine the compressibility of dried powdered fruits of Piper guineense with a view to determining the suitability of its formulation into tablet dosage form. The compressional properties was studied in comparison with that of microcrystalline cellulose, dicalcium phosphate dihydrate and corn starch BP using density measurements and the Heckel and Kawakita equations for the analysis of the compression data at dwell times 5, 15 and 30s. The Heckel plots showed that the P. guineense powder is a Type A material and the degree of onset of plastic deformation increases as the dwell time is increased. Piper guineense exhibited the fastest onset of plastic deformation at 30s dwell time and the overall amount of plastic deformation was higher for Piper guineense than cornstarch and dicalcium phosphate dihydrate at all dwell times. The overall amount of plastic deformation for Piper guineense was highest at 15s dwell time. Results suggest that it should be of significant benefit to use a dwell time of 15s for the compression of Piper guineense powder.Key words: Piper guineense, cornstarch, microcrystalline cellulose, dwell time, compressional characteristics